Accurate force and moment measurement in spring testing machines by an integrated hexapod-shaped multicomponent force transducer. (26th July 2018) - Genta, Gianfranco; Prato, Andrea; Mazzoleni, Fabrizio; Germak, Alessandro; Galetto, Maurizio
Abstract: In spring testing machines, measurement of transversal forces and bending/torsion moments, as well as vertical force, is crucial for spring characterization. For this purpose, the more advanced industrial machines are typically equipped with multicomponent force transducers (MFTs), composed by different sensors each one is dedicated to a single force component. However, such assembled MTFs present unsolved technical problems, i.e. moment measurements are not performed and the periodic calibration is hard to manage. To overcome these problems, a hexapod-shaped MFT was devised and integrated into a new model of an industrial spring testing machine, thus enabling simple periodic calibrations and ensuring measurement traceability, as well as measuring the moment components. The present work deals with the performance evaluation and metrological validation of the system.